Determinants of Green Energy Technology Purchase Intention: An Analytical Study - Ali, Imran; Naushad, Mohammad (International Journal of Energy Economics and Policy, 2023)
Intensive use of non-renewable resources like coal and crude oil has created several issues and challenges such as the worsening greenhouse effect, depletion of fossil fuels, air pollution, global warming, and climate change. A few remedies have been implemented to address these issues caused by the heavy use of nonrenewable fuels. Developing and adopting green energy technologies is a step in the same direction. Green energy technologies have the potential to reduce the world’s carbon footprint, and waste and increase the efficiency of energy production. This can lead consumers to save money and the environment. This research work intends to determine important factors affecting the purchase intention of green energy technologies. There are four independent variables and one dependent variable. Data was collected from 342 randomly selected respondents from Delhi and NCR. Structural Equation Modeling (SEM) was used to analyze collected data. The main findings of this study are that perceived risk and functional factors impact the consumers’ green technology purchase intention substantially.